A Brief Review of Internal Inconsistencies in General Relativity Theory (GRT) and Comparisons to Metric Theory of Gravity (MTG) - Jaroslav Hynecek (Innovations in Science and Technology Vol. 7, 2022)
This paper is written mostly in an overview style in its nature thus avoiding many equations and computations, which casual readers do not necessarily understand. Paper investigates and compares side by side in detail assumptions with their logical consequences and resulting internal inconsistencies in both; the General Relativity Theory and the Metric Theory of Gravity. It is found that the GRT has many such internal inconsistencies, which have to be corrected by unusual and difficult to believe assumptions that are not backed up by a typical experience one encounters in a real life, while the MTG avoids such problems. For the readers who are interested in proofs of discussed findings the paper provides internet links to papers where such proofs are available. The key differences between the GRT and MTG theories are: the gravitational mass dependence on velocity, nature of the “empty” space, the finite or infinite size of the Universe, the existence of Black Holes (BH) with their Event Horizons (EH), the creation of Universe by the Big Bang (BB), and the relation between the Cosmic Microwave Background Radiation (CMBR) temperature, and the Hubble constant that characterizes the velocity of receding Galaxies.